2020
DOI: 10.1088/1757-899x/928/2/022068
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development of Highly Flowable Cementitious Grouts for Semi-flexible Pavement Mixture

Abstract: Grout is a substance with a cement which is characterized by a high strength and it is a high workability, so it can be injected in places of small cracks or places of water leakage. Generally, it is used to repair cracks or defects of concrete, also it can be used to fill the voids under the metal bases or digging anchors. Moreover, grout is used efficiently in the process of production the semi-flexible pavement mixtures. The purpose of this study is to design a sustainable grout using waste and by-products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Figure 4 shows the compressive strength for pastes at different W/B ratios. The mixtures from M0 to M3 showed that the compressive strength increases for all mixtures with increasing age because cement needs time to complete its hydration process and reach relatively mature strength [16]. This is interesting as SF normally increases the compressive strength of the concrete mix.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Figure 4 shows the compressive strength for pastes at different W/B ratios. The mixtures from M0 to M3 showed that the compressive strength increases for all mixtures with increasing age because cement needs time to complete its hydration process and reach relatively mature strength [16]. This is interesting as SF normally increases the compressive strength of the concrete mix.…”
Section: Resultsmentioning
confidence: 86%
“…-------Uniformlythoroughly coated CONMIX provided silica fume (SF). SF, also known as condensed silica fume or micro silica, is a fine powder with a high concentration of amorphous silicon dioxide [16]. This substance is a byproduct of the smelting of silicon and ferrosilicon [37].…”
Section: Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation